Dasar Pertimbangan Hakim dalam Putusan Perceraian karena Perselisihan Rumah Tangga (Studi Kasus di Pengadilan Agama Praya) - Irawan Muda, Lalu (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine and analyze the underlying considerations of the panel of judges in rendering divorce decisions due to ongoing domestic disputes at the Religious Court of Praya, Central Lombok. Continuous conflict is recognized as a valid legal ground for divorce petitions under Article 19 letter (f) of Government Regulation No. 9 of 1975 and Article 116 of the Compilation of Islamic Law. This research employs a juridical-empirical approach using a case study method on several judicial decisions related to divorce cases throughout 2023. Data were obtained through court decision documents and interviews with the presiding judges. The findings reveal that the judges’ considerations include evidence of irreconcilable prolonged conflict, the absence of the respondent during trial sessions, witness testimonies supporting the petitioner’s claims, and the judges’ concern for the welfare of the children and the wife. The decisions also reflect the application of principles of justice, humanity, and protection of women's rights after divorce. The study recommends optimizing mediation mechanisms and enhancing the application of maqāṣid al-sharī‘ah perspectives in the practice of Islamic family adjudication.